2000
DOI: 10.1115/1.1343910
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Flaws Under Biaxial Loading Conditions—Part I: The Effect of Specimen Size on Fracture Toughness Values Obtained From Large-Scale Cruciform Specimens1

Abstract: A technology to determine shallow-flaw fracture toughness of reactor pressure vessel (RPV) steels is being developed. This technology is for application to the safety assessment of RPVs containing postulated shallow-surface flaws. It has been shown that relaxation of crack-tip constraint causes shallow-flaw fracture toughness of RPV material to have a higher mean value than that for deep flaws in the lower transition temperature region. Cruciform beam specimens developed at Oak Ridge National Laboratory (ORNL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Extensive experiments were also performed in the Oak Ridge National Laboratory to study the mixed effect of in-plane and out-of-plane constraint (McAfee et al, 2001;Williams et al, 2001). This work consisted of two sets of experiments on cleavage fracture of A533B steel.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experiments were also performed in the Oak Ridge National Laboratory to study the mixed effect of in-plane and out-of-plane constraint (McAfee et al, 2001;Williams et al, 2001). This work consisted of two sets of experiments on cleavage fracture of A533B steel.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed effect of low in‐plane and high out‐of‐plane constraint has received some attention, for example notable experiments were performed in the Oak Ridge National Laboratory 22–26 . The Oak Ridge National Laboratory work consisted of two sets of experiments on cleavage fracture of A533B steel.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear then that there is uncertainty in the effectiveness of biaxial loading on shallow cracks to demonstrate an effect of out‐of‐plane loading. Some researchers believe they found an effect of biaxial loading 22–28 whereas others observed no change 29,30,32 . Because most of the experimental investigations were performed using FPB cruciform specimens in bending, shallow cracks had to be introduced in the specimens which led to a mixed effect of low in and high out‐of‐plane constraint.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of T z on 3D crack-front fields and fracture toughness were systematically studied by Guo. [25][26][27] In addition, the mixed effect of low in-plane and high out-of-plane constraint have received some attention 28,29 : it was found that the shallow crack effect is reduced if the specimen was tested under high outof-plane constraint conditions. Now, 3D effects has been received much attention.…”
Section: Introductionmentioning
confidence: 99%